Crtc1 Deficiency Causes Obesity Potentially via Regulating PPARγ Pathway in White Adipose - Hu, Yimeng; Lv, Jian; Fang, Yu; Luo, Qiang; He, Yuan; Li, Lili; Fan, Mingxia; Wang, Zhihua (Frontiers in Cell and Developmental Biology, 2021)
Obesity is characterized by excessive fat accumulation and associated with glucose and lipid metabolism disorders. Crtc1, a transcription cofactor regulating CREB activity, has been involved in the pathogenesis of metabolic syndrome; however, the underlying mechanism remains under debate. Here we generated a Crtc1-/- mouse line using the CRISPR/Cas9 system. Under normal feeding conditions, Crtc1-/- mice exhibited an obese phenotype resultant from the abnormal expansion of the white adipocytes. The development of obesity in Crtc1-/- mice is independent of alterations in food intake or energy expenditure. Moreover, Crtc1-/- mice were more prone to insulin resistance and dyslipidemia, as evidenced by higher levels of plasma glucose, insulin and FABP4 than wildtype mice. Transcriptome analysis in liver and epididymal white adipose tissue (eWAT) showed that the fat accumulation caused by Crtc1 deletion was mainly related to lipid metabolism in adipose tissue, but not in liver. GSEA and KEGG analysis identified PPAR pathway to be of the highest impact on lipid metabolism in eWAT. This regulation was independent of a direct interaction between CRTC1 and PPARγ. Our findings demonstrate a crucial role of Crtc1 in regulating lipid metabolism in adipose during development, and provide novel insights into obesity prevention and therapeutics.